2004
DOI: 10.1002/prep.200400025
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials for Heterogeneous Combustion

Abstract: Nanophase materials and nanocomposites, characterized by an ultra fine grain size (less than 100 nm) have attracted wide spread interest in recent years by virtue of their unusual mechanical, electrical, optical, magnetic, and energetic properties. Studies have shown that the thermal behavior of nano‐scaled materials is quite different from micron‐sized powders. Nanosized metallic and explosive powders have been used as solid propellant and explosive mixtures to increase efficiency. At the same time recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(72 citation statements)
references
References 7 publications
1
69
0
Order By: Relevance
“…These traits could be advantageous for propellants. Pivkina et al [77] has shown that nano-sized particles of RDX react exothermically at lower temperatures from DTA measurements than micron-sized particles of RDX. Pressed strands of nano-sized RDX burned faster at pressures above 10 MPa as well.…”
Section: Figure 16mentioning
confidence: 99%
See 1 more Smart Citation
“…These traits could be advantageous for propellants. Pivkina et al [77] has shown that nano-sized particles of RDX react exothermically at lower temperatures from DTA measurements than micron-sized particles of RDX. Pressed strands of nano-sized RDX burned faster at pressures above 10 MPa as well.…”
Section: Figure 16mentioning
confidence: 99%
“…Micronsized Al particles have a higher ignition temperature (~ 2350 K) [120] and a tendency to agglomerate in solid rocket motor (SRM) environments [123]. In the recent past, nano-scale materials and composites, characterized by ultra fine grain sizes, have been recognized for their unusual energetic properties such as increased catalytic activity and higher reactivity [124]. In the hope of engineering a novel nano-energetic material, extensive research efforts have been made to study the burning behavior of nano-Al (nAl) particles in various oxidizer environments [125][126][127].…”
Section: Ii27 Multi-scale Modeling Of Nano-aluminum Particle Ignitimentioning
confidence: 99%
“…According to the research conducted in 1997 by Ivanov and Tepper (1997), aluminum nanoparticles could increase the burning rate of the charge in comparison with microparticles. Furthermore, nanoparticles application in fuel demonstrated shorter ignition delay in combustion process when compared to that of microparticles (Pivkina et al 2004). Moreover, nanoparticles featuring high surface area to volume ratio lead to more contact area between fuel and oxidizer (De Luca et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast,d issolutiona nd the subsequent recrystallizationp otentially allows crystals to grow free of stress. Methods included in this categorya re sol-gel processes [12],v acuum-condensation [ 14],e lectrospray [15],u ltrasound assisted nanocrystallization, and RapidE xpansion of SupercriticalS olutions (RESS) [5].T hese techniques are discontinuous or expensive processes, therefore they are not suitable for industrial production.R isse et al proposed the Spray FlashE vaporation (SFE)f or continuous nanostructured particles production [ 16,17].T he latterr epresents an effective and innovative process that consists in heating up as olution of the energetic material and exposing it to an important and high pressure drop. Subsequently the solvent evaporates immediately,t he dissolvedm aterialc ompletely crystallizes and is recovered by cyclones as ad ry ultrafine powder.T his specific technique has been used successfullyt op roduce n-HMX [10] and moreover,t op roduce nanometric cocrystals for medical or energetic applications [18].…”
Section: Introductionmentioning
confidence: 99%